Persepsi Ustadz Ponpes Darul Makmur Sungai Cubadak terhadap Pembayaran Zakat Fitrah untuk Pembangunan Mushalla (Studi Kasus di Nagari Sungai Cubadak Kecamatan Baso) - Ferdi Ilham; Saiful Amin (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Zakat al-Fitr is an obligation for every Muslim, with the primary purpose of assisting those entitled to receive it (mustahiq), particularly the poor and needy. However, in practice in the village of Sungai Cubadak, some members of the community channel their Zakat al-Fitr toward the construction of a mosque, leading to differing viewpoints among religious leaders. This study aims to examine the practice of using Zakat Fitrah payments for mosque construction and to analyze the perceptions of the ustadz at Darul Makmur Islamic Boarding School regarding this practice. The research method employed is field research using a qualitative approach, involving data collection techniques such as interviews, observations, and literature review, followed by inductive and normative analysis. The results indicate that the payment of zakat al-fitr for mosque construction is carried out by handing over the zakat to mosque administrators, who are considered gharimin. Meanwhile, the ustadz’s perceptions vary; some permit it under certain conditions, such as for the public good or in emergency situations, while others reject it because it does not align with the provisions regarding the recipients of zakat al-fitr, which prioritize the poor and needy.The conclusion of this study is that the practice of using zakat al-fitr payments for the construction of prayer halls remains a subject of debate, with a general consensus that such funds are more appropriately distributed to the primary recipients (mustahiq) in accordance with Islamic law, except in specific emergency situations that meet the principle of public interest.